Method for producing gelatinous cellulose material and method for producing secondary cellulose material

By optimizing the molar ratio of water and zinc chloride and pretreatment of sodium bicarbonate, the high energy consumption and high viscosity problems of common industrial cellulose products in the prior art are solved, and a method for efficient production of gel-like cellulose materials is realized. It is suitable for cellulose products such as NBKP, LBKP and BDIP.

JP2025058473AInactive Publication Date: 2025-04-09CO LTD HUANGYI
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023168431
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-28
Publication Date
2025-04-09
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The prior art mainly uses special Avicel-marked wood pulp cellulose products to produce gel-like cellulose materials, but fails to make full use of the common industrial cellulose products such as NBKP, LBKP and BDIP, and has high energy consumption and low efficiency during the production process.

Method used

Using a solvent composed of water and zinc chloride, the mole ratio of zinc chloride (the molar ratio of water: zinc chloride is between 3.70:1 and 4.25:1) and concentration, combined with pretreatment using sodium bicarbonate solution, reduce the viscosity of cellulose products, thereby improving the production efficiency of gel-like cellulose materials.

Benefits of technology

Through optimizing the process, the viscosity of cellulose products can be effectively reduced and the production efficiency of gel-like cellulose materials can be improved. It is suitable for industrially common cellulose products such as NBKP, LBKP and BDIP, and the cost is more economical.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025058473000003
    Figure 2025058473000003
  • Figure 2025058473000004
    Figure 2025058473000004
  • Figure 2025058473000005
    Figure 2025058473000005
Patent Text Reader

Abstract

To provide a method for producing a gelatinous cellulose material for which an optimum use amount of zinc chloride in a solvent is calculated from a concentration of used pulp, and a method for producing a secondary cellulose material.SOLUTION: A method for producing a gelatinous cellulose material includes a solvent preparation step of preparing a zinc chloride solvent for dissolving unbleached or bleached chemical pulp obtained from a soda cooking method or a kraft cooking method, and a dissolution step of dissolving the pulp in the zinc chloride solvent for treatment. In the solvent preparation step, the solvent is prepared with a molar ratio of water and zinc chloride in the range from 3.70:1 to 4.25:1, and in the dissolution procedure, the pulp is dissolved so that the pulp concentration is 3 to 7%.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a gel-like cellulose material and a method for producing a secondary cellulose material. [Background technology]

[0002] Wood, non-wood grasses, bamboo, etc. are natural plants, and unbleached kraft pulp (UKP) is obtained by the kraft cooking process (KP), and bleached pulp (BKP) is obtained by bleaching the pulp with bleaching agents such as chlorine dioxide, oxygen, and hydrogen peroxide. Bleached kraft pulp from softwood and hardwood is abbreviated as NBKP and LBKP, respectively. NBKP and LBKP are more than 98% cellulose, with the remaining 2% or less being lignin, processed materials, and other impurities.

[0003] The unbleached and bleached pulp mentioned above are used to make various types of paper that we use in our daily lives. After that, it becomes waste, is collected, and is then re-cooked and re-bleached to become bleached deinked pulp (BDIP).

[0004] The above pulps (NBKP, LBKP, BDIP) are, of course, natural substances, and the cellulose in these pulps becomes cellulose I. When treated with a high-concentration alkaline solution, cellulose I becomes cellulose II. The crystallinity of cellulose I and II is different. When natural cellulose (cellulose I) is treated with a caustic soda concentration of 10% or more, the crystallinity and crystallinity index of the cellulose decrease, but the OH stretching vibration increases (cellulose II) (see Non-Patent Document 1 below).

[0005] As mentioned above, there are many ways to utilize cellulose, and many areas remain unexplored. For example, zinc chloride solution is sometimes used as a solvent to dissolve cellulose. The following results have been reported in academic papers on zinc chloride solution:

[0006] The group of Xu et al. used Avicel (registered trademark) pulp and produced a gel-like cellulose material under conditions of a reaction temperature of 65°C, a zinc chloride concentration of 68%, and a pulp concentration of 10.5% (see Non-Patent Document 2 below). The group of Lara-Serrano et al. also used Avicel (registered trademark) pulp and produced a gel-like cellulose material under conditions of a reaction temperature of 70°C, a pulp concentration of 10%, and an amount of water used that was 1.9 times the amount of zinc chloride used (see Non-Patent Document 3 below).

[0007] In the above academic paper, the pulp concentration (10.0-10.5%) used was high, so the amount of mixing energy required in the production process of gel-like cellulose material was high. Furthermore, the amount of zinc chloride used was variable among researchers.

[0008] These academic papers use special Avicel (registered trademark) pulp and do not consider the general kraft pulp or recycled waste paper pulp used in the paper pulp industry in Japan or abroad, nor do they consider analysis of the components of the obtained gel-like cellulose material or methods of use.

[0009] On the other hand, the technology described in the following Patent Document 1 (hereinafter referred to as the Patent Document 1 invention) uses Avicel (registered trademark) pulp to produce a micro- or nanocrystalline cellulose composition. The production process is as follows. In step (A), the pulp is contacted with a first solvent. The first solvent is a 40 to 65 wt % ZnCl2 solution. In the next contact step (B), the amorphous cellulose phase is dissolved, thereby dissolving the amorphous cellulose phase preferentially over the crystalline cellulose phase. Step (C) includes a step of separating the dissolved amorphous cellulose from the crystalline cellulose. The obtained micro- or nano-cellulose has a cellulose I structure, which is then contacted with a second solvent containing 65 to 90 wt % ZnCl2 in water, to obtain delaminated cellulose of a cellulose II structure. [Prior art documents] [Patent documents]

[0010] [Patent Document 1] Special Publication No. 2022-529955 [Non-patent literature]

[0011] [Non-Patent Document 1] Transitional properties of cotton fibers from cellulose I to cellulose II structure, Yue, Y., Han, G., and Wu, Q. (2013).(https: / / bioresources.cnr.ncsu.edu / resources / transitional-properties-of-cotton-fibers-from-cellulose-i-to-cellulose-ii-structure / ) [Non-Patent Document 2] A facile route to prepare cellulose-based films, Qin Xu a, Chen Chen, Katelyn Rosswurm, Tianming Yao, Srinivas Janaswamy(https: / / doi.org / 10.1016 / j.carbpol.2016.04.114) [Non-Patent Document 3] High enhancement of the hydrolysis rate of cellulose after pretreatment with inorganic salt hydrates, Marta Lara-Serrano, Silvia Morales-delaRosa, Jose M. Campos-Martin, Jose LG Fierro(https: / / doi.org / 10.1039 / D0GC01066A) Summary of the Invention [Problem to be solved by the invention]

[0012] All of these academic papers (Non-Patent Documents 1 to 3) and the publicly known invention (Patent Document 1) use special Avicel (registered trademark) pulp, and do not consider kraft pulp, recycled paper pulp, etc., which are commonly used in the paper pulp industry in Japan and abroad.

[0013] In the case of the industrially produced pulp discussed above, such as kraft pulp and recycled waste paper pulp, it is necessary to study means for achieving more efficient productivity of gel-like cellulose materials.

[0014] Furthermore, the above academic paper does not discuss the component analysis or the method of use of the obtained gel-like cellulose material.

[0015] As mentioned above, Avicel® pulp used in the reference academic paper is microcrystalline cellulose, which is an alpha cellulose excipient produced by acid hydrolysis of special wood pulp, purified, and partially depolymerized. Therefore, Avicel® pulp is expensive and is considered to be economically unsuitable as a material for gel-like cellulose. For this reason, the present invention provides a method for producing gel-like cellulose material using commercially available pulps NBKP (bleached softwood kraft pulp), LBKP (bleached hardwood kraft pulp), and BDIP (bleached recycled waste paper pulp).

[0016] The present invention has been proposed in consideration of the above-mentioned situation, and provides a method for producing a gel-like cellulose material in which the optimal amount of zinc chloride to be used in the solvent is calculated from the concentration of the pulp used to produce the gel-like cellulose material, and a method for producing secondary cellulose materials (coagulated derivatives, precipitated substances in organic solvents, etc.). [Means for solving the problem]

[0017] In order to achieve the above-mentioned object, the method for producing a gel-like cellulose material of the present invention is a method for producing a gel-like cellulose material by going through a solvent preparation step of preparing a solvent for dissolving pulp and a dissolution step of dissolving the pulp in the solvent and processing it, characterized in that in the solvent preparation step, the solvent is water and zinc chloride, the molar ratio of the water to the zinc chloride is in the range of 3.70:1 to 4.25:1, and in the dissolution step, the pulp is dissolved in the solvent to achieve the desired pulp concentration.

[0018] The method for producing a gel-like cellulose material according to the present invention is characterized in that, prior to the dissolving step, the pulp is subjected to a treatment step of pretreating the pulp with an aqueous sodium hydroxide solution.

[0019] The method for producing a gel-like cellulose material of the present invention is characterized in that, in the treatment procedure, by immersing the pulp in the sodium hydroxide aqueous solution, the viscosity of the gel-like cellulose material is reduced compared to an untreated gel-like cellulose material, which is a gel-like cellulose material produced without undergoing the treatment procedure, and the pulp concentration is 3 to 7%.

[0020] In the method for producing a gel-like cellulose material of the present invention, the sodium hydroxide aqueous solution has a sodium hydroxide concentration of 7 to 10%, a temperature of 55 to 75°C, and an addition amount of 10 ml per 1 g of the pulp, and the treatment procedure is characterized in that the pulp is immersed in the sodium hydroxide aqueous solution for 1 to 3 hours.

[0021] The method for producing a gel-like cellulose material according to the present invention is characterized in that, in the dissolving step, the pulp is dissolved in the solvent, and then the temperature is adjusted to 50 to 80°C and the mixture is allowed to stand for 2 to 8 hours while stirring.

[0022] The method for producing a cellulose gel material according to the present invention is characterized in that in the solvent preparation step, the solvent is made to contain lithium chloride, and the molar ratio of the zinc chloride to the lithium chloride is set to 9.0:1.0 to 9.5:0.5.

[0023] The method for producing a secondary cellulose material according to the present invention is characterized in that a gel-like cellulose material produced by the above-mentioned method for producing a gel-like cellulose material is introduced into an organic solvent selected from 99.5% ethanol, 95% ethanol, acetone, chloroform, a nonionic surfactant, an anionic surfactant, water, methanol, diethyl ether or 1,4-dioxane to obtain a secondary cellulose material which is a precipitate of cellulose II.

[0024] The method for producing a secondary cellulose material according to the present invention is characterized in that the gel-like cellulose material produced by the above-mentioned method for producing a gel-like cellulose material is covered with one or more organic solvents selected from 95% ethanol, 99.5% ethanol and diethyl ether, and stored at -4°C to obtain a secondary cellulose material which is a solidified substance.

[0025] The method for producing a cellulose gel material according to the present invention is characterized in that the pulp is either soda pulp or kraft pulp, which is an unbleached chemical pulp. Effect of the Invention

[0026] Therefore, in producing a gel-like cellulose material, the optimal amount of zinc chloride to be used in the solvent can be calculated based on the concentration of the pulp used. [Brief description of the drawings]

[0027] [Figure 1]Fig. 1 shows photographs of NBKP cellulose gel materials produced by the method for producing a cellulose gel material according to the first embodiment of the present invention. Fig. 1(a) is a photograph of a cellulose gel material with a pulp concentration of 2%, Fig. 1(b) is a photograph of a cellulose gel material with a pulp concentration of 3%, Fig. 1(c) is a photograph of a cellulose gel material with a pulp concentration of 4%, Fig. 1(d) is a photograph of a cellulose gel material with a pulp concentration of 5%, Fig. 1(e) is a photograph of a cellulose gel material with a pulp concentration of 6%, and Fig. 1(f) is a photograph of a cellulose gel material with a pulp concentration of 8%. [Diagram 2] Fig. 2 is a photograph of an NBKP gel-like cellulose material produced by the method for producing a gel-like cellulose material according to the first embodiment of the present invention, and an NBKP gel-like cellulose material produced by the method for producing a gel-like cellulose material according to the second embodiment of the present invention. Fig. 2(a) is a photograph of a gel-like cellulose material with a pulp concentration of 3% that has not been subjected to a treatment procedure, Fig. 2(b) is a photograph of a gel-like cellulose material with a pulp concentration of 3% that has been subjected to a treatment procedure, Fig. 2(c) is a photograph of a gel-like cellulose material with a pulp concentration of 5% that has been subjected to a treatment procedure, and Fig. 2(d) is a photograph of a gel-like cellulose material with a pulp concentration of 7% that has been subjected to a treatment procedure. [Diagram 3] 3 is a photograph of a cellulose gel material of LBKP produced by the method for producing a cellulose gel material according to the first embodiment of the present invention, a cellulose gel material of LBKP produced by the method for producing a cellulose gel material according to the second embodiment, a cellulose gel material of BDIP produced by the method for producing a cellulose gel material according to the first embodiment, and a cellulose gel material of BDIP produced by the method for producing a cellulose gel material according to the second embodiment. Fig. 3(a) is a photograph of a cellulose gel material of LBKP with a pulp concentration of 2.5% that has not been subjected to a treatment procedure, Fig. 3(b) is a photograph of a cellulose gel material of LBKP with a pulp concentration of 3% that has been subjected to a treatment procedure, Fig. 3(c) is a photograph of a cellulose gel material of BDIP with a pulp concentration of 1.75% that has not been subjected to a treatment procedure, and Fig. 3(d) is a photograph of a cellulose gel material of BDIP with a pulp concentration of 3% that has been subjected to a treatment procedure. [Figure 4]Fig. 4 is a photograph of a gel cellulose material produced by the method for producing a gel cellulose material according to the third embodiment of the present invention. Fig. 4(a) is a photograph of a gel cellulose material of zinc chloride:copper chloride (divalent) (9.0:1.0), Fig. 4(b) is a photograph of a gel cellulose material of zinc chloride:copper chloride (divalent) (9.5:0.5), Fig. 4(c) is a photograph of a gel cellulose material of zinc chloride:copper chloride (divalent) (9.5:0.5), Fig. 4(d) is a photograph of a gel cellulose material of zinc chloride:copper chloride (monovalent) (9.0:1.0), Fig. 4(e) is a photograph of a gel cellulose material of zinc chloride:copper chloride (monovalent) (9.0:1.0), and Fig. 4(f) is a photograph of a gel cellulose material of zinc chloride:lithium chloride (9.0:1.0). [Diagram 5] Fig. 5 is a photograph of a cellulose gel material produced by a method for producing a cellulose gel material according to a third embodiment of the present invention. Fig. 5(a) is a photograph of a cellulose gel material of zinc chloride:cobalt chloride (9.5:0.5), Fig. 5(b) is a photograph of a cellulose gel material of zinc chloride:cobalt chloride (9.5:0.5), Fig. 5(c) is a photograph of a cellulose gel material of zinc chloride:manganese chloride (9.0:1.0), and Fig. 5(d) is a photograph of a cellulose gel material of zinc chloride:nickel chloride (9.5:0.5). [Figure 6] Fig. 6 is a photograph of a secondary cellulose material produced by a method for producing a secondary cellulose material according to an embodiment of the present invention. Fig. 6(a) is a photograph of a secondary cellulose material produced by soaking a gel-like cellulose material of NBKP in 95% ethanol, Fig. 6(b) is a photograph of a secondary cellulose material produced by soaking a gel-like cellulose material of NBKP in 99.5% ethanol, Fig. 6(c) is a photograph of a secondary cellulose material produced by soaking a gel-like cellulose material of NBKP in acetone, Fig. 6(d) is a photograph of a secondary cellulose material produced by soaking a gel-like cellulose material of NBKP in water, Fig. 6(e) is a photograph of a secondary cellulose material produced by soaking a gel-like cellulose material of NBKP in an anion, and Fig. 6(f) is a photograph of a secondary cellulose material produced by soaking a gel-like cellulose material of NBKP in a nonion. [Figure 7]Fig. 7 is a photograph of a secondary cellulose material produced by a method for producing a secondary cellulose material according to an embodiment of the present invention. Fig. 7(a) is a photograph of a secondary cellulose material produced by immersing an NBKP gel-like cellulose material in methanol, Fig. 7(b) is a photograph of a secondary cellulose material produced by immersing an NBKP gel-like cellulose material in diethyl ether, Fig. 7(c) is a photograph of a secondary cellulose material produced by immersing an NBKP gel-like cellulose material in 1,4-dioxane, and Fig. 7(d) is a photograph of a secondary cellulose material produced by immersing an NBKP gel-like cellulose material in chloroform. [Figure 8] Fig. 8 is a photograph of a secondary cellulose material produced by the method for producing a secondary cellulose material according to an embodiment of the present invention. Fig. 8(a) is a photograph of a secondary cellulose material obtained from a gel-like cellulose material of NBKP and a photograph of the secondary cellulose material soaked in 95% ethanol, Fig. 8(b) is a photograph of a secondary cellulose material obtained from a gel-like cellulose material of LBKP and a photograph of the secondary cellulose material soaked in 95% ethanol, and Fig. 8(c) is a photograph of a secondary cellulose material obtained from a gel-like cellulose material of BDIP and a photograph of the secondary cellulose material soaked in 95% ethanol. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0028] A method for producing a cellulose gel material according to an embodiment of the present invention will be described below.

[0029] First Embodiment In this embodiment, pulp is treated with zinc chloride to obtain a gel-like cellulose material. The pH of the obtained gel-like cellulose material is about 1, so that cellulose I in the pulp is oxidized and decomposed to produce a gel-like cellulose material of cellulose II. Zinc chloride reacts with water to produce hydrochloric acid, as shown in the following reaction equation: (https: / / doi.org / 10.1002 / jps.3080070807) ZnCl2+ H2O → HCl + Zn(OH)Cl Since the pH of the obtained gel-like cellulose material is 1, it is presumed that the produced hydrochloric acid hydrolyzes the cellulose I in the pulp to produce cellulose II, similar to other inorganic acids such as sulfuric acid and nitric acid. Therefore, the gel-like cellulose material of this embodiment is cellulose II, and its derivatives, such as the coagulated substance and the secondary cellulose material that is a substance precipitated in an organic solvent, are also cellulose II.

[0030] The method for producing a gel-like cellulose material in this embodiment involves producing a gel-like cellulose material through a solvent preparation step of preparing a solvent for dissolving pulp, and a dissolution step of dissolving pulp in the solvent and processing it, in which the solvent preparation step uses water and zinc chloride as the solvent, and in the dissolution step, pulp is dissolved in the solvent to achieve the desired pulp concentration.

[0031] In the dissolving procedure, the temperature of the solvent after the pulp is dissolved is set to 50° C. to 80° C., more preferably 60° C. to 75° C. The dissolving time is set to 2 to 8 hours, preferably 3 to 6 hours.

[0032] In the method for producing a gelled cellulose material according to this embodiment, once the pulp concentration is determined, the amount of water used can be calculated. This can be obtained by dividing the bone dry weight (not including water) of the pulp used by the pulp concentration used. The number of moles of water is calculated from this amount of water used (amount of water used ÷ molecular weight of water), and the number of moles of water obtained is divided by 4 to obtain the number of moles of zinc chloride used (generally, the amount of zinc chloride used is 1 / 4 of the amount of water used). The amount of zinc chloride used can be calculated from the calculated number of moles of zinc chloride and the molecular weight of zinc chloride.

[0033] The following example shows how to calculate the weight of added water, the weight of zinc chloride used, etc. 1) If the pulp used is NBKP, the bone dry weight of NBKP used is 3g (if the moisture content of the pulp is 25%, the amount of pulp containing moisture = 3 ÷ 0.25 = 12g, the amount of moisture in the pulp = 12-3 = 9ml or 9g). 2) If the gelling concentration is 3%, then the amount of water required for the gelling reaction = 3 g of pulp ÷ 0.03, the concentration at gelling = 100 ml or the number of moles of water = 100 ÷ 18 = 5.556 moles (molecular weight of water: 18). 3) Amount of water added = 100ml - 9ml = 91ml 4) Number of moles of zinc chloride needed = 5.556 moles ÷ 4 = 1.389 moles 5) Amount of zinc chloride required = 1.389 mol × 136 g / mol = 188.9 g; Calculate. Therefore, the molar ratio of water to zinc chloride is 5.556:1.389=4:1. Since the concentration of zinc chloride for dissolving cellulose pulp is generally 70 to 80%, the molar ratio of water to zinc chloride is preferably in the range of 3.70:1 to 4.25:1.

[0034] The test procedure is as follows: Put 91 ml of distilled water into a glass beaker, add 188.9 g of anhydrous zinc chloride little by little while stirring with a stirrer until it is completely dissolved. Since this reaction generates heat, safety must be taken into consideration.

[0035] While the dissolved zinc chloride liquid is still hot, slowly add the pulp to the beaker in small portions, and each time the pulp dissolves, slowly add the torn pulp to the beaker. After 3 g of pulp is completely dissolved, the glass beaker is moved to a constant temperature bath at 65°C and left for 6 hours while stirring with a mixer at 450-650 rpm. When the reaction is complete, the beaker is removed from the constant temperature bath and left to cool to room temperature. The resulting gel-like cellulose material is transparent. Figure 1 (Effect of pulp concentration on NBKP gel-like cellulose material, reaction temperature: 65°C, reaction time: 6 hours) shows photographs of gel-like cellulose materials using NBKP at different pulp concentrations. When the pulp concentration is 2-3%, the material is mostly transparent, although it is slightly yellow. As the pulp concentration increases, the yellow color deepens and the viscosity increases. When the pulp concentration exceeds 5%, it is no longer transparent, and when it exceeds 6%, it becomes yellowish white and becomes so viscous that it is difficult to stir.

[0036] The method for producing a gel-like cellulose material from LBKP or BDIP pulp and the method for calculating the amount of water and zinc chloride required for production are the same as those for NBKP pulp described above.

[0037] However, for the same amount of pulp used (3 g), the pulp concentration of LBKP and BDIP was 2.5% and 1.75%, respectively, which was lower than the pulp concentration of NBKP at gelation (3%), which was 3%. As already mentioned, as the pulp concentration increases, the viscosity of the gel also increases. For this reason, in order to achieve the desired pulp concentration (e.g., 3%) in the gelation of LBKP and BDIP, the amount of water and zinc chloride used is much higher than that of NBKP. Therefore, it is considered that the conditions of the gelation reaction change depending on the type of pulp. For this reason, the pulp quality of NBKP, LBKP, and BDIP was analyzed. As shown in Table 1, NBKP has a lower α-cellulose content and a higher hemicellulose content of β- and γ-cellulose than LBKP and BDIP, so the pulp concentration of NBKP at gelation was a high value of 3%.

[0038] [Table 1]

[0039] Second Embodiment In the second embodiment, prior to the dissolution step, the pulp is pretreated with an aqueous sodium hydroxide solution to remove impurities such as residual lignin and residual hemicellulose in the pulp, and then a treatment step is performed to process high-purity cellulose.

[0040] The pulp is pretreated under the sodium hydroxide treatment conditions of a temperature of 65°C (50 to 70°C, 55 to 75°C), a 10% (7 to 15%) sodium hydroxide solution, an addition amount of sodium hydroxide solution of 10 ml / g of pulp, and a treatment time of 2 hours (1 to 3 hours), and then the pulp is filtered and washed with water.The pulp is then washed with diluted hydrochloric acid (about 0.5 to 1%), preferably with a 10% acetic acid solution, and further washed with water until the pH of the filtrate reaches 6 to 7.

[0041] The analysis results of LBKP, NBKP, and BDIP treated with 10% sodium hydroxide are shown in Table 1. The lignin content and hemicellulose content (β- and γ-cellulose) of these pulps have been almost completely removed, while the α-cellulose content has increased.

[0042] When NBKP untreated with 10% sodium hydroxide (NBKP that has not undergone a treatment procedure) is used as a gel-like cellulose material, the appropriate pulp concentration is about 3%, and when it exceeds 5%, the viscosity increases. However, as shown in Figure 2 (increase in pulp concentration from 3% to 5% and 7% when producing a gel-like cellulose material from NBKP after 10% caustic soda treatment (reaction temperature: 65°C, reaction time: 6 hours)), when a gel-like cellulose material is produced from NBKP treated with 10% sodium hydroxide (NBKP that has undergone a treatment procedure), it is almost transparent and the viscosity is suppressed even at pulp concentrations of 5% and 7%. This makes it possible to reduce the amount of water used and the amount of zinc chloride added, etc.

[0043] As shown in Figure 3 (effect of improving pulp concentration when producing a gel-like cellulose material from LBKP and BDIP after 10% caustic soda treatment (reaction temperature: 65°C, reaction time: 6 hours)), the pulp concentration of the gel-like cellulose material reaction from LBKP treated with 10% sodium hydroxide was 3%, which is higher than the concentration of 2.5% for the original LBKP. Similarly, in BDIP, the pulp concentration of the gel-like cellulose material reaction from 10% sodium hydroxide treatment improved from 1.75% to 3%, making it possible to reduce the amount of water used and the amount of zinc chloride added, etc.

[0044] By using NBKP treated with 10% sodium hydroxide, it is possible to produce a gel-like cellulose material even when the pulp concentration is 5% or 7%, so similarly, by using LBKP and BDIP treated with sodium hydroxide, it is possible to produce a gel-like cellulose material even when the pulp concentration is 5% or 7%.

[0045] The gel-like cellulose material produced with NBKP, LBKP, and BDIP treated with 10% sodium hydroxide at a pulp concentration of 7% moves slowly when stirred, so the limiting pulp concentration of these pulps is estimated to be 10%. That is, when it exceeds 10%, the viscosity of the gel becomes so high that stirring becomes difficult. This result is lower than the 10 to 10.5% of Avicel (registered trademark) pulp in the above reference. This is because NBKP, LBKP, and BDIP have a long fiber length of 0.1 to 1.5 mm compared to the fiber length of Avicel (registered trademark) pulp of up to 50 μm, and the pulp viscosity is also high.

[0046] <Third embodiment> In the method for producing a gelled cellulose material according to the present embodiment, chlorides of monovalent copper, divalent copper, manganese, nickel, cobalt, lithium, etc., which can partially replace the amount of zinc chloride used, are used. Of these chlorides, only lithium can be used as a substitute. If a metal compound other than lithium is used, a secondary cellulose material, which is a solidified product of a derivative, is obtained.

[0047] Heavy metals commonly used in automotive batteries, such as copper, manganese, nickel, cobalt, and lithium, were partially substituted for zinc chloride during the preparation of the cellulose gel material, and the state of the resulting cellulose gel material was examined.

[0048] As shown in Figures 4 and 5 (Effect of metal compounds on the production of gel-like cellulose material of NBKP), chlorides of monovalent copper, divalent copper, manganese, nickel, cobalt, lithium, etc. were substituted with 5-10% of zinc chloride on a molar basis at a pulp concentration of 3%.

[0049] When the mixture was ZnCl2:CuCl2 = 9.0:1.0 (reaction temperature: 65°C) (Figure 4(a)), the mixture turned dark brown and solidified. When the mixture was ZnCl2:CuCl2 = 9.5:0.5 (reaction temperature: 65°C) (Figure 4(b)), the mixture turned dark brown and solidified. When the mixture was ZnCl2:CuCl2 = 9.5:0.5 (reaction temperature: room temperature) (Figure 4(c)), the mixture turned ochre and solidified. When the mixture was ZnCl2:CuCl = 9.0:1.0 (reaction temperature: 65°C) (Figure 4(d)), the mixture turned orange and solidified. When the mixture was ZnCl2:CuCl = 9.0:1.0 (reaction temperature: room temperature) (Figure 4(e)), the mixture turned white and solidified. In the case of ZnCl2:LiCl=9.0:1.0 (reaction temperature: 65°C) (Figure 4(f)), the solution was light brown but transparent and mostly liquid (gel-like).

[0050] When the mixture was ZnCl2:CoCl2 = 9.5:0.5 (reaction temperature: 65°C) (Fig. 5(a)), it turned dark brown and solidified. When the mixture was ZnCl2:CoCl2 = 9.5:0.5 (reaction temperature: room temperature) (Fig. 5(b)), it turned dark brown and solidified. When the mixture was ZnCl2:MnCl2 = 9.0:1.5 (reaction temperature: 65°C) (Fig. 5(c)), it turned light brown and solidified. When the mixture was ZnCl2:NiCl2 = 9.5:0.5 (reaction temperature: 65°C) (Fig. 5(d)), it turned green and solidified.

[0051] Therefore, the influence of the mixed metal chloride on the gel cellulose material is that the gel cellulose material obtained from the heavy metals other than lithium is colored or solidified. Therefore, only lithium is mixed with zinc chloride to produce a gel cellulose material. The molar ratio of zinc chloride to lithium is preferably 9.0:1.0 to 9.5:0.5. Note that although the gel cellulose material shown in Figures 4 and 5 has not been subjected to a treatment procedure, it may be one that has been subjected to a treatment procedure.

[0052] The results of examining the components of the produced cellulose gel material are shown in Table 2 below. The cellulose gel material was neutralized with a 25% caustic soda solution, filtered through filter paper, and thoroughly washed with water. The resulting residue was air-dried and incinerated at 750°C. As shown in Table 2, the ash content of the cellulose gel materials used, NBKP, LBKP, and BDIP, was 75-80%, and the cellulose content was 20-25%. Therefore, the method of using the cellulose gel material is centered on the metal (zinc, etc.) in the gel.

[0053] [Table 2]

[0054] <Secondary Cellulose Material> A secondary cellulose material was prepared as a precipitation material in an organic solvent using the gel-like cellulose material (pulp concentration 3%) produced according to the second embodiment. The produced gel-like cellulose material requires purification. For this reason, the precipitation property of the produced gel-like cellulose material in an organic solvent was examined. It was confirmed that the produced gel-like cellulose material precipitated in eight organic solvent precipitation media, namely 99.5% ethanol, 95% ethanol, acetone, chloroform, water, methanol, diethyl ether, and 1,4-dioxane, and two precipitation media, a nonionic surfactant and an anionic surfactant, which were used as precipitation media.

[0055] The gel-like cellulose material was gradually added to these precipitation media while stirring with a stir bar to produce a precipitate. The resulting precipitate was purified cellulose II, which is the gel-like cellulose material.

[0056] The resulting gel-like cellulose material precipitated in organic solvents was transparent and large strand-like in acetone, 95% ethanol, 99.5% ethanol, etc., white and small strand-like in chloroform, nonionic surfactant, anionic surfactant, and fine particles in water. The results are shown in Figure 6 (precipitation of gel-like cellulose material of NBKP in organic solvents after 10% caustic soda treatment).

[0057] When the precipitation medium was water, the precipitate was white fine particles but the supernatant was a cloudy solution.

[0058] When the precipitation medium was methanol, the precipitate was dispersed throughout the medium and appeared as white, thread-like floating matter.

[0059] When the precipitation medium was diethyl ether or 1,4-dioxane, the precipitates accumulated in small strands at the bottom of the beaker. The results are shown in Figure 7 (precipitation of gel-like cellulose material of NBKP into organic solvents after treatment with 10% caustic soda).

[0060] A gel-like cellulose material (pulp concentration 3%) obtained by the second embodiment was used to prepare a solidified material as a secondary cellulose material. The gel-like cellulose material obtained from NBKP, LBKP, and BDIP treated with 10% caustic soda was poured into approximately 95% of the volume of each transparent container of a petri dish. The remaining 5% of the volume of the petri dish was filled with one of the organic solvents, 95% ethanol, 99.5% ethanol, or diethyl ether.

[0061] The surface of the gel-like cellulose material is covered with an organic solvent obtained by using diethyl ether, 95% ethanol, or 99.5% ethanol alone, or a combination of diethyl ether and 95% ethanol or diethyl ether and 99.5% ethanol, and placed in a freezing cabinet (-4°C) in a household refrigerator overnight. A solidified material is obtained the next day.

[0062] The solidified materials of NBKP, LBKP, and BDIP used are shown in Figure 8 (solid gels produced from gel-like cellulose materials of NBKP, LBKP, and BDIP after treatment with 10% caustic soda). To preserve the solidified materials, they were soaked in 95% ethanol (upper photograph of the figure).

[0063] The above results are for bleached softwood kraft pulp (NBKP), bleached hardwood kraft pulp (LBKP), and bleached deinked pulp from recycled waste paper (BDIP), but it is estimated that similar results will be obtained for unbleached softwood kraft pulp (NUKP) treated with 10% caustic soda solution, unbleached hardwood kraft pulp (LUKP), unbleached deinked pulp from recycled waste paper (UDIP), unbleached chemical pulp (soda pulp) treated with caustic soda solution, bleached kraft pulp, and unbleached chemical kraft pulp.The secondary cellulose material may be the gel-like cellulose material obtained by the first embodiment.

[0064] Although the embodiment of the present invention has been described in detail above, the present invention is not limited to the above embodiment, and various design modifications can be made to the present invention without departing from the scope of the claims.

Claims

1. a solvent preparation step for preparing a solvent for dissolving the pulp; A method for producing a gel-like cellulose material, comprising: a dissolving step of dissolving the pulp in the solvent and processing the pulp; and the solvent preparation step comprising: the solvent being water and zinc chloride; and a molar ratio of the water to the zinc chloride being in the range of 3.70:1 to 4.25:1; The dissolving step comprises dissolving the pulp in the solvent to a desired pulp consistency; 5. A method for producing a cellulose gel material comprising the steps of:

2. Prior to said lysis procedure, A treatment step is performed in which the pulp is pretreated with an aqueous sodium hydroxide solution. A method for producing a gel-like cellulose material according to claim 1.

3. In the treatment procedure, the pulp is immersed in the sodium hydroxide aqueous solution, The gel-like cellulose material has a lower viscosity than a non-treated gel-like cellulose material that is a gel-like cellulose material produced without undergoing the treatment procedure, and the pulp concentration is 3 to 7%.

3. The method for producing a gel-like cellulose material according to claim 2.

4. The sodium hydroxide aqueous solution is The concentration of the sodium hydroxide is 7 to 10%, the temperature is 55 to 75° C., and the amount of the sodium hydroxide added is 10 ml per 1 g of the pulp. In the treatment procedure, the pulp is immersed in the sodium hydroxide aqueous solution for 1 to 3 hours. A method for producing a gel-like cellulose material according to claim 3.

5. In the dissolving step, the pulp is dissolved in the solvent, and then the temperature is set to 50 to 80° C. and the mixture is left for 2 to 8 hours while being stirred. A method for producing a gel-like cellulose material according to claim 4.

6. In the solvent preparation step, lithium chloride is added to the solvent, and a molar ratio of the zinc chloride to the lithium chloride is set to 9.0:1.0 to 9.5:0.

5. A method for producing a gel-like cellulose material according to any one of claims 1 to 5.

7. A gel-like cellulose material produced by the method for producing a gel-like cellulose material according to any one of claims 1 to 5 is poured into an organic solvent selected from 99.5% ethanol, 95% ethanol, acetone, chloroform, a nonionic surfactant, an anionic surfactant, water, methanol, diethyl ether, and 1,4-dioxane to obtain a secondary cellulose material which is a precipitate of cellulose II.

2. A method for producing a secondary cellulose material comprising the steps of:

8. The gel-like cellulose material produced by the method for producing a gel-like cellulose material according to any one of claims 1 to 5 is covered with one or more organic solvents selected from 95% ethanol, 99.5% ethanol and diethyl ether, and stored at -4°C to obtain a secondary cellulose material, which is a solidified substance.

2. A method for producing a secondary cellulose material comprising the steps of:

9. The pulp is either soda pulp or kraft pulp, which is an unbleached chemical pulp; A method for producing a gel-like cellulose material according to claim 1.

Citation Information

Patent Citations

  • Method for producing micro- or nanocrystalline cellulose

    JP2022529955A